Retrospective Study of Factors Potentially Influencing Occurrence of Cough in Slovak Patients with Sarcoidosis. (2nd June 2019) - Kovacova, Eva; Vysehradsky, Robert; Kocan, Ivan; Plevkova, Jana; Buday, Tomas
Abstract : Introduction . Sarcoidosis is a multisystem granulomatous disease of unknown aetiology, commonly involving the lungs. Cough is a frequent and troublesome symptom of sarcoidosis that reduces patients' quality of life. Aim . Retrospective analysis of different factors—smoking history, Scadding stage, results of lung function testing, calcium metabolism, endobronchial finding, CD4+/CD8+ T-cell ratio in bronchoalveolar lavage fluid (BALF), and other sarcoidosis symptoms in relationship to presence/absence of cough in sarcoidosis patients. Methods . We retrospectively studied sarcoidosis patients diagnosed at the Clinic of Pneumology and Phthisiology of Martin University Hospital between 1998 and 2018. Patients with a history of cough-relevant comorbidities were excluded from the study. GraphPad Prism 7.0 software was used to perform statistical analysis. Results . 101 sarcoidosis patients were included to the study: 65 patients reporting from cough and 36 without cough. The cough was slightly more frequent in nonsmokers (p = 0.166 ) and in women (p = 0.688 ). Cough was associated with dyspnoea (p = 0.0007 ), fever (p = 0.0324 ), and chest pain (p = 0.0206 ) and did not associate with arthralgia (p = 0.317 ) and erythema nodosum (p = 0.505 ). Patients with cough had significantly a lower average value of calciuria (p = 0.0014 ) and lower MEF25 (p = 0.0304 ), MEF50 (p = 0.0061 ), FEV1 (p = 0.0025 ), and FVC (p = 0.0025 ) in % of predicted values, and more often positive endobronchial finding (p = 0.0206 ), compared to patients without cough. Calcemia, FEV1/FVC, DLCO, and CD4+/CD8+ T-cell ratio in BALF and occurrence of cough did not differ between different stages of the disease. Conclusions . We found significant differences between sarcoidosis patients with/without cough regarding symptoms, results of lung function tests, endobronchial finding, and calcium metabolism. Further research is needed to understand the etiopathogenesis of cough in sarcoidosis patients.